Induced Hepatic Glutathione and Metabolomic Alterations Following Mixed Pesticide and Fertilizer Exposures in Juvenile Leopard Frogs (Lithobates sphenocephala). (29th December 2021) - Van Meter, Robin J.; Glinski, Donna A.; Purucker, S. Thomas; Henderson, W. Matthew
Abstract: The increasing use of agrochemicals, alone and in combination, has been implicated as a potential causative factor in the decline of amphibians worldwide. Fertilizers and pesticides are frequently combined into single‐use tank mixtures for agricultural applications to decrease costs while meeting the food demands of a growing human population. Limited data are available on the effects of increased nitrogen levels in nontarget species, such as amphibians, and therefore investigating alterations in the nitrogen cycle and its impacts on amphibians needs to be considered in best management practices going forward. The objective of the present study was to elucidate the impact of fertilizer (urea) and herbicide (atrazine and/or alachlor) tank mixtures on the hepatic metabolome of juvenile leopard frogs as well as to investigate alterations in oxidative stress by relating these changes to glutathione (GSH) levels. Herbicide exposure only moderately increased this parameter in amphibians, however, urea alone and in combination with either atrazine or alachlor statistically elevated GSH levels. Interestingly, urea also inhibited pesticide uptake: calculated bioconcentration factors were greatly decreased for atrazine and alachlor when urea was present in the exposure mixture. Metabolomic profiling identified fluxes in hepatic metabolites that are involved in GSH and carbohydrate metabolic processes as well as altered intermediates in the urea cycle. Ultimately, understanding the biological impacts of nitrogenous fertilizers alone and in combination with pesticide exposure will inform best management practices to conserve declining amphibian populations worldwide. Environ Toxicol Chem 2022;41:122–133. © 2021 SETAC